Las Tic como estrategia metodológica para el aprendizaje de ecuaciones lineales de primer grado con una incógnita en el noveno año de la unidad educativa José Peralta de la ciudad de Cañar, año lectivo 2015-2016. - Andrade Pillaga, Julio Aníbal (2016)
This research originated in the need to solve the difficulties of student of 9th year of General Basic Education (GBE) when developing activities related to solving linear equations of the first degree with one unknown variable. Because of this, was raised as a general objective: to analyze how ICT as methodological strategies affect learning of linear equations of the first degree with one unknown variable in the ninth year of GBE of the Education Unit Temporary “Jose Peralta” of the city of Cañar. Methodologically this study was quasi-experimental, field, relational prospective and analytical. The methods used were the descriptive, deductive and quantitative. We worked with all 45 students attending the 9th year of GBE of the Education Unit Temporary “Jose Peralta”, who were applied a test designed exclusively for this study, which sought to measure the level of impact of ICT in learning linear equations. The main conclusion was obtained that the use of ICT as a methodological strategy significantly affects the learning of linear equations of the first degree with one unknown variable by students in the ninth year of Basic Education of the Education Unit Temporary “Jose Peralta”.